1984
DOI: 10.1016/0035-9203(84)90225-6
|View full text |Cite
|
Sign up to set email alerts
|

Histological evolution of caecal lesions in experimental amoebiasis

Abstract: Histopathological studies in guinea-pigs infected intracaecally with Entamoeba histolytica were carried out longitudinally on days 3, 7, 11, 15, 20 and 35 after infection. Three characteristic modes of development of caecal lesions were observed. These in order of their prevalence were the classical inflammatory cellular infiltration, lymphoid hypertrophy and necrotizing colitis. Occasional amoeboma formation was observed in progesterone-treated animals. This is the first time that histological lesions which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although both the humoral and cellular immune apparatus was sensitized to sperm and seminal plasma antigens, no change was observed in the counts of T, B and ET cells. Gill et al (1984) and Ganguly et al (1979) have reported that even with relatively low T cell counts it is possible to obtain blastogenic responses that are higher than baseline if sensitization to antigen has occurred. With regard to the B cell count, no clear cut explanation is forthcoming from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although both the humoral and cellular immune apparatus was sensitized to sperm and seminal plasma antigens, no change was observed in the counts of T, B and ET cells. Gill et al (1984) and Ganguly et al (1979) have reported that even with relatively low T cell counts it is possible to obtain blastogenic responses that are higher than baseline if sensitization to antigen has occurred. With regard to the B cell count, no clear cut explanation is forthcoming from the present study.…”
Section: Discussionmentioning
confidence: 99%